The Role of Startups in Digitalization and Innovative Develop-ment of Economy - Nikolaevna Likhacheva, Olga; Germanovna Pashtova, Lelya; Alexandrovna Setchenkova, Liubov; Alexandrovna Slepneva, Tatiana; ., . (International Journal of Engineering and Technology, 2018)
The article examines the potential of introduction of new digital technologies in the Russian market through the development of startups in the modern economy. The article considers the key drivers of growth of digital startups and the prospects for their development in the domestic market of Russia and establishes the role of progressively developing information sphere for the investments of venture units of large corporations, business angels, the largest investment funds and other investors in the world economy. The peculiarities of startups' development in the Russian economy in modern conditions are revealed and the most significant solutions of this problem are presented.Â Â Â